Group treatments for sensitive health care problems: a randomised controlled trial of group versus individual physiotherapy sessions for female urinary incontinence - Lamb, S; Pepper, J; Lall, R; Jørstad-Stein, E; Clark, MD; Hill, L; Fereday-Smith, J (BioMed Central, 2009)
Background: The aim was to compare effectiveness of group versus individual sessions of physiotherapy in terms of symptoms, quality of life, and costs, and to investigate the effect of patient preference on uptake and outcome of treatment. Methods: A pragmatic, multi-centre randomised controlled trial in five British National Health Service physiotherapy departments. 174 women with stress and/or urge incontinence were randomised to receive treatment from a physiotherapist delivered in a group or individual setting over three weekly sessions. Outcome were measured as Symptom Severity Index; Incontinence-related Quality of Life questionnaire; National Health Service costs, and out of pocket expenses. Results: The majority of women expressed no preference (55%) or preference for individual treatment (36%). Treatment attendance was good, with similar attendance with both service delivery models. Overall, there were no statistically significant differences in symptom severity or quality of life outcomes between the models. Over 85% of women reported a subjective benefit of treatment, with a slightly higher rating in the individual compared with the group setting. When all health care costs were considered, average cost per patient was lower for group sessions (Mean cost difference £52.91 95%, confidence interval (£25.82 - £80.00)). Conclusion: Indications are that whilst some women may have an initial preference for individual treatment, there are no substantial differences in the symptom, quality of life outcomes or non-attendance. Because of the significant difference in mean cost, group treatment is recommended. Trial Registration Trial Registration number: ISRCTN 16772662